PENGELOLAAN KONFLIK POLITIK DI DESA ARANG LIMBUNG KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - hendayana s.stp (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2020)
The background of this research is the Management of Political Conflict in Arang Limbung Village, Sungai Raya District, Kubu Raya Regency, where the conflict that occurs is due to groups that are pro and contra for the change in the status of Arang Limbung village to become a sub-district. The purpose of this research is to identify and find solutions to the problems faced, especially those related to the political conflict that occurred in the village of Arang Limbung. This research uses a descriptive method and the data analysis used is the qualitative analysis which is a process of simplifying data into a form that is easier to read and interpret. The conclusion from this observation is that there are still problems of political conflict in Arang Limbung Village from various interests of a group of people who are pros and cons of changing the status of the Arang Limbung village to a Kelurahan. With this research, it is hoped that all political conflicts in the village of Arang Limbung can be resolved by finding the best solution in order to create conditions that are conducive, safe, and peaceful in Arang Limbung Village.